2021
DOI: 10.3390/plants10081743
|View full text |Cite
|
Sign up to set email alerts
|

P2K1 Receptor, Heterotrimeric Gα Protein and CNGC2/4 Are Involved in Extracellular ATP-Promoted Ion Influx in the Pollen of Arabidopsis thaliana

Abstract: As an apoplastic signal, extracellular ATP (eATP) is involved in plant growth and development. eATP promotes tobacco pollen germination (PG) and pollen tube growth (PTG) by stimulating Ca2+ or K+ absorption. Nevertheless, the mechanisms underlying eATP-stimulated ion uptake and their role in PG and PTG are still unclear. Here, ATP addition was found to modulate PG and PTG in 34 plant species and showed a promoting effect in most of these species. Furthermore, by using Arabidopsis thaliana as a model, the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…Generally, most of the highly expressed GhCNGCs showed higher levels in reproductive tissues than vegetative tissues, implicating that GhCNGCs may be critical to cotton reproduction. For example, GhCNGC1, 13, 18, and 32 were expressed most highly in ovules (0, 1, 20 DPA), anther, filament, petal and sepal; their closest homologs are AtCNGC2 and AtCNGC4 in Arabidopsis (Figure 1), which play important functions in the regulation of floral transition [66,68], pollen growth [69], thermal sensing and acquired thermotolerance [66], senescence and programmed cell death [70][71][72], and innate immune response [65,73]. Interestingly, GhCNGC17, 33, 37, and 39 increased expression levels during the developmental stage from 10 to 25 DPA (Figure 7A), likely contributing to fiber development.…”
Section: Expression Profiles Of the Cngc Family Genes During Growth A...mentioning
confidence: 99%
“…Generally, most of the highly expressed GhCNGCs showed higher levels in reproductive tissues than vegetative tissues, implicating that GhCNGCs may be critical to cotton reproduction. For example, GhCNGC1, 13, 18, and 32 were expressed most highly in ovules (0, 1, 20 DPA), anther, filament, petal and sepal; their closest homologs are AtCNGC2 and AtCNGC4 in Arabidopsis (Figure 1), which play important functions in the regulation of floral transition [66,68], pollen growth [69], thermal sensing and acquired thermotolerance [66], senescence and programmed cell death [70][71][72], and innate immune response [65,73]. Interestingly, GhCNGC17, 33, 37, and 39 increased expression levels during the developmental stage from 10 to 25 DPA (Figure 7A), likely contributing to fiber development.…”
Section: Expression Profiles Of the Cngc Family Genes During Growth A...mentioning
confidence: 99%
“…eATP is now reported to act upstream of CNGC2. Wu et al (2021) reported that eATP (0.1 mM) failed to elicit a plasma membrane Ca 2+ -permeable influx conductance in Arabidopsis pollen grain protoplasts of a cngc2 mutant. This concentration of eATP stimulated pollen germination in the wild type but not cngc2 ( Wu et al, 2021 ), but it remains unknown whether activation of CNGC2 by eATP would increase [Ca 2+ ] cyt .…”
Section: Cngc2 Is Implicated In Cotyledon Eatp-induced [Ca 2+ ] Cyt Increasementioning
confidence: 99%
“… Wu et al (2021) reported that eATP (0.1 mM) failed to elicit a plasma membrane Ca 2+ -permeable influx conductance in Arabidopsis pollen grain protoplasts of a cngc2 mutant. This concentration of eATP stimulated pollen germination in the wild type but not cngc2 ( Wu et al, 2021 ), but it remains unknown whether activation of CNGC2 by eATP would increase [Ca 2+ ] cyt . Here, the cngc2 loss of function mutant defense not death 1 ( dnd1 ; which constitutively expresses cytosolic (apo)aequorin as a luminescent [Ca 2+ ] cyt reporter, Qi et al, 2010 ) was tested for impaired eATP-induced [Ca 2+ ] cyt increase.…”
Section: Cngc2 Is Implicated In Cotyledon Eatp-induced [Ca 2+ ] Cyt Increasementioning
confidence: 99%
See 2 more Smart Citations